KONSEP GARAP NGGANTUNG DALAM KARAWITAN GAYA SURAKARTA - Leica De lovi Mistortoify; Muhammad Nur Salim; Harun Isma'il (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
This study discusses the phenomenon, symbols, and meaning of garap nggantung in the context of Surakarta-style gamelan performances. Data were collected through observation, interviews, and literature studies. The method used is qualitative descriptive analysis. In this study, the focus of the analysis is on the phenomenon, symbols, and meanings related to garap nggantung. This study reveals that garap nggantung is the result of a complex creative process, involving balungan notation, interaction between instruments, and individual interpretations of the gamelan player. Garap nggantung is not only a technique, but also a symbol that contains deep meaning. This finding has important implications for the teaching and preservation of Surakarta-style gamelan. By understanding the meaning behind garap nggantung, gamelan learners can better understand the aesthetic richness of gamelan art. In addition, this study also opens up opportunities for further research on other garaps in gamelan texts in depth.